Jawbone fibrous dysplasia: retrospective evaluation in a cases series surgically treated and short review of the literature: Jawbone fibrous dysplasia: retrospective data analysis - Pacino, Gino Amleto; Cocuzza, Salvatore; Tonoli , Giovanni; Boscolo Rizzo , Paolo; Tirelli , Giancarlo; Tofanelli , Margherita; Ciprandi , Giorgio; La Mantia, Ignazio; Maniaci, Antonino; Da Mosto , Maria Cristina; Spinato, Giacomo (Acta Biomedica Atenei Parmensis, 2020)
Background and aim of the work. Fibrous dysplasia is a fibro-osseous osteopathy in which the normal bone architecture is replaced by fibrous tissue and non-functional trabeculae-like osseous structures. In head and neck area monostotic or polyostotic lesions cause a progressively expanding destructive bone swelling producing cosmetic deformities and functional impairments. The aim of this article is to present a retrospective review of a clinical case series with pathologically confirmed jawbone fibrous dysplasia for over an 8-year-period.Material and Methods. Clinical presentation and radiographic features of fibrous dysplasia affecting the jawbone skeletal area, surgical procedures performed including the reconstructive methods employed and clinical outcomes were analysed for each patient.Results. Seven cases were classified as having monostotic fibrous dysplasia while the others four cases were classified as having polyostotic form. The mandible was most commonly involved. The most common presenting features included marked facial deformity, intraoral bulging, malocclusion and dental alterations. Aesthetic and/or functional impairments were the major indications for surgical treatment in all the patients of this series. Six patients underwent bone remodelling while in the remaining cases subtotal or total resection was performed. Bone reconstruction by means of autologous free bone grafts or revascularized free bone flaps was made in three cases.Conclusion. The choice of the tailored therapeutic approach should be evaluated according the patient’s age, rate of growth, anatomic location, type of involvement and the presence or not of functional disturbances and cosmetic alterations. Surgery remains the best therapeutic option.